Circularly polarized dual-band resonance in a miniaturized implantable antenna using combined hexagonal and rhombic patches - Shanmugam Kumaravel; Madurakavi Karthikeyan (Scientific Reports)
Abstract The design and characterisation of a novel dual-band implantable antenna with compact size is presented in this research. The antenna, which is $$5 × 5 × 0.635 {\text{mm}}^{3}$$ in size and operates at two critical frequencies—0.954 GHz in the UHF band and 2.4 GHz in the ISM band—was fabricated on an RT6010 substrate. The U-shaped slot and shorting pin on the radiating element have been exploited to achieved dual-band and circular polarization. The antenna is noteworthy for achieving circular polarization with a broad axial ratio bandwidth of 24.6%, which enables strong performance throughout its operating frequencies. The proposed antennas SAR values satisfy IEEE safety standards for implantable medical devices with a gain of − 28.1 dB at 2.4 GHz and − 31.2 dB at 0.954 GHz, despite its small size. The design represents a significant advancement in the field of medical implant technology since it prioritizes effective wireless communication capabilities while upholding strict safety regulations.